Importance of E-Governance in Transforming Technical Education in India - Kulkarni, D. M.; Mahajan, N. S.; Pakhare, J. D.; Kheradkar, V. V. (Journal of Engineering Education Transformations, 2025)
Governance and leadership play a crucial role in development and progress of technical institutes in India, a developing country. During the last decade, there has been a mushrooming growth in technical institutions. This growth has not been accompanied by maturity in governance and leadership. Statutory bodies like UGC, AICTE, Technical education department of state governments, Universities have failed to protect the interest of all the stakeholders, particularly the most important stakeholder, the students. There is a lack of continuity in policies, rules, guidelines, which leads to confusion in the minds of the stakeholders. Lack of transparency and procedural clarities play a role. Today, we are living in an information economy, where governance and leadership have to be dynamic and responsive to the needs of the stakeholders. E-governance, if implemented in correct spirit, can be a game changer, as it will lead to transparency, accountability, empowerment, processes, security and most important accountability. Modern information technology can be successfully harnessed to provide a dynamic repository of rules and regulations to all the stakeholders. This will improve quality of decision making and benefit the students. The paper suggests how e-governance can be used at different levels to ensure the transformation of technical education in India.